2010
DOI: 10.1093/ntr/ntq114
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and electronic cigarettes (e-cigarettes) have different smoking characteristics

Abstract: Generally, e-cigarettes required stronger vacuums (suction) to smoke than conventional brands, and the effects of this on human health could be adverse. The amount of aerosol produced by e-cigarettes decreased during smoking, which necessitated increasing puff strength to produce aerosol. The decreased efficiency of aerosol production during e-cigarette smoking makes dosing nonuniform over time and calls into question their usefulness as nicotine delivery devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
176
0
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 6 publications
3
176
0
7
Order By: Relevance
“…The original EC consisted of a cartridge with nicotine-containing fluid and an atomizer which aerosolized the cartridge fluid when heated by a battery (Trtchounian et al, 2010). In many newer models, the cartridge and atomizer are combined into a single unit, termed a ''cartomizer'' (Williams and Talbot, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original EC consisted of a cartridge with nicotine-containing fluid and an atomizer which aerosolized the cartridge fluid when heated by a battery (Trtchounian et al, 2010). In many newer models, the cartridge and atomizer are combined into a single unit, termed a ''cartomizer'' (Williams and Talbot, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Used cartomizers can be replaced or refilled with fresh fluid, referred to as refill fluid (Bahl et al, 2012). Although the basic design of EC is similar across brands, significant variation in performance exists between and within brands (Trtchounian et al, 2010;Williams and Talbot, 2011). EC and their associated products are sold in shops, malls, and online where age verification is not always needed, making these products relatively accessible.…”
Section: Introductionmentioning
confidence: 99%
“…For example, e-cigarette and tobacco cigarette puffing characteristics differ (Trtchounian et al, 2011); there is a learning curve to efficient vaping (McQueen et al, 2011); and regular users tend to use second rather than first generation devices (Dawkins et al, 2013;Foulds, Veldheer & Berg, 2011). In order to determine whether user experience and/or characteristics of the e-cigarette itself might influence blood nicotine delivery, Vansickel and Eissenberg (2013) carried out a pragmatic test in eight experienced e-cigarette users who used their own preferred devices and strength of nicotine cartridges.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study found unsafe levels of acetaldehyde in a brand of e-cigarettes [9]. Further, electronic cigarettes have been shown to require stronger and stronger vacuums (increase puff strength) to create vapor as the amount of fluid decreases with use [10]. The variability of the puff strength varied with the brand of electronic cigarette tested.…”
Section: Discussionmentioning
confidence: 99%